2018
DOI: 10.1167/iovs.18-25307
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of Abicipar-Pegol, an Anti-VEGF DARPin Therapeutic That Potently Inhibits Angiogenesis and Vascular Permeability

Abstract: PURPOSE. DARPin molecules are a novel class of small proteins that contain engineered ankyrin repeat domain(s) and bind to target proteins with high specificity and affinity. Abicipar-pegol (abicipar), a DARPin molecule targeting vascular endothelial growth factor-A (VEGF-A), is currently under evaluation in patients with age-related macular degeneration. The pharmacodynamic properties of abicipar were characterized using in vivo and in vitro assays. METHODS. The binding affinity of abicipar was assessed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 56 publications
0
47
0
1
Order By: Relevance
“…In addition, the 2 mg, 16week (Q16) were simulated to test the feasibility of the 4month interval. The simulated vitreous exposure was compared with in vitro and in vivo IC 50 values estimated from a HUVEC-sprouting assay (0.017 nM) (Rodrigues et al, 2018) and from AH VEGF data (6 nM) obtained from patients with DME treated with abicipar, respectively. After both a Q8 and Q12 dosing regimen, mean steadystate minimal concentrations (C min,ss ) were maintained above the upper end of the IC 50 range (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, the 2 mg, 16week (Q16) were simulated to test the feasibility of the 4month interval. The simulated vitreous exposure was compared with in vitro and in vivo IC 50 values estimated from a HUVEC-sprouting assay (0.017 nM) (Rodrigues et al, 2018) and from AH VEGF data (6 nM) obtained from patients with DME treated with abicipar, respectively. After both a Q8 and Q12 dosing regimen, mean steadystate minimal concentrations (C min,ss ) were maintained above the upper end of the IC 50 range (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Both 1 or 2 mg of abicipar produced greater improvements in best-corrected visual acuity with fewer IVT injections administered than 0.5 mg ranibizumab (Callanan et al, 2018). In the CEDAR and SEQUOIA identical phase III studies, abicipar (2 mg 8week or quarterly dosing) demonstrated noninferiority compared with ranibizumab (0.5 mg dosed monthly) on the primary endpoint of stable vision at week 52 (Rodrigues et al, 2018). The purpose of this analysis is to develop a translational pharmacokinetic/pharmacodynamic (PK/ PD) model of abicipar to provide a quantitative understanding of the drug disposition and target engagement in the rabbit and use the model to translate to humans to explore the feasibility of longer dosing intervals in the clinic.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…This suggests that this new drug can also be used as a therapeutic agent with a longer duration and less frequent injections. 5,6 The number of patients in need of an anti-VEGF treatment is expected to dramatically increase in the coming years due to new indications and an aging population. 7 Recently, data from the DRCR.net Protocol S study have led to the approval of ranibizumab for the treatment of proliferative diabetic retinopathy.…”
Section: Introductionmentioning
confidence: 99%